A NON-DESTRUCTIVE SEED SAMPLING METHOD FOR HIGH THROUGHPUT GENOTYPING IN GROUNDNUT - HARI KISHAN SUDINI, MURALI T VARIATH, DNYANESHWAR B. DESHMUKH, SUNIL CHAUDHARI BALRAM MARATHI,CH. V. DURGA RANI (The Journal of Research, PJTSAU, 2019)
The routine isolation of plant genomic DNA uses leaf tissues for genotyping in Marker Assisted Selection (MAS). This requires time and resources for planting the segregating material, logistics of labeling and sampling in the field and harvesting the selected plants. We describe here a simple, non-destructive sampling method for genomic DNA isolation from a mature dry groundnut seed. For the comparative study, the leaf disc and seed chips of 46 genotypes were sent to Intertek Pvt. Ltd for DNA isolation and genotyping. The DNA isolation yielded a mean concentration of 16.8 ng/Âµl and 31.8 ng/Âµl from seed and leaf tissues, respectively with A260/A280 ratio of 1.9 (mean) for both the samples. The isolated DNA was genotyped using the Kompetitive allele-specific PCR assay with 10 SNPs associated with resistance to late leaf spot, rust, and high oleic acid. The KASP assay resulted in a 97% allele calls in the DNA isolated from seed and leaf tissues. The quality of DNA isolated from seed chips was functionally comparable to DNA extracted from leaf disc which gave the similar results in KASP assay. This method is non-destructive and useful for MAS to screen segregating population for targeted traits prior to planting which enables to minimize resources.